Exploring the Meaning of “Religion” in Its Various Applications in the Quran - Abbas Ismaeelizadeh (آموزه‌های قرآنی, 2012)
The root of the term “religion” and its derivatives have been used hundred and one times in the Quran: ritual and Sharia, punishment and reward and debt. The first meaning is when this word takes the form of “din” and the second meaning is when it takes the form of “madin” and composition of determined and determiner of “Yowm-al-Din” has come in the meaning of “The Day of Judgment” and the third meaning is when it takes the form of “dain”. Meanwhile, in four verses of the Quran (Al-Zariyat, Al-Infitar, Al-Tin and Al-Ma’un) that the word “din” has been used, more translators and interpreters unlike the other cases of the application of the term, it is understood as a meaning other than ritual and religious law. But the careful study and understanding of these verses prove that in these cases, especially in the last three verses like the other applications of this word in the Quran, has been used in the meaning of “ritual, religious law, and Islam” and in chapter of Zariyat this meaning is dominating.